Genetic progress of the milking Gyr herd of Umbuzeiro, PB, Brazil - dos Santos, Elson Soares; Leite, Paulo Roberto de Miranda; Lôbo, Raysildo Barbosa; Durães, Marcus Cordeiro (Pesquisa Agropecuaria Brasileira, 2014)
Genetic progress was evaluated in a milking Gyr herd in Umbuzeiro, Paraíba, Brazil. Data from 1,049 lactations of 329 cows mated to 32 bulls were analysed by least squares and maximum likelihood methods. It was observed significative influence (P <0,01) of year and month of calving on the lactation length and milk yield. The best lactations length and milk yields were observed for cows that calved from October to April, mainly for cows that calved in February (yield of 1,542 ± 69 kg/year and lactation length of 241 ± 8 days). Repeatability estimates for lactation length and milk yield were 0.37 ± 0.04 and 0.57 ± 0.03, respectively. In same order, heritability coefficients (paternal half-sibs correlation method) were 0.023 ± 0.043 and 0.37 ± 0.13). Genetic and phenotypic correlations between these characteristics were 0.903 ± 0.022 and 0.807. Annual genetic and phenotypic trends were 0.53 and 3.4 days for lactation length and 6.55 and 30.55 kg for milk yield. Modest genetic gain obtained for milk yield (0.52% in relation to overall mean per year) suggests the necessity of increase in the selection pressure for yield, in the herd studied.